SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN DI SMU DENGAN LOGIKA FUZZY - M. Taufiq Tamam; Arif Johar Taufiq; Fathul Amri (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2011)
High School (SMU) as one of the educational institutions in Indonesia, has a range of issues and problems faced in running the learning process. One of the problems facing the system of placement of students in high school. Placement of students of this school system is influenced by student grades, student talents, and interests of students. If something goes wrong in choosing majors might be devastating for students if it does not match the capabilities, talents and interests. For that we need the existence of a specific decision support system to process the placement of students in high school second grade. The decision making process of this major election is determined by using fuzzy logic. Where in decision making, fuzzy logic will determine the declared value of membership if it fulfills the criteria for membership will be included in the specified department or not. This application is designed to provide ease in decision-making by performing calculations based on the report card process, aptitude tests, and student interest. Keywords: decision support systems, fuzzy logic, the placement of students in high school.